Living Reality of the Syrian Refugees outside the Jordanian Refugee Camps “An attempt to reveal the incentives to stay and return” (Journal of Namibian Studies : History Politics Culture, 2023)
The current study aims to identify the security, economic and social incentives that motivate the Syrian refugees living outside Jordanian asylum camps to stay in Jordan, and the incentives of return to homeland at the same time. The study adopted the descriptive method and designed a questionnaire as an instrument to collect data, where statistical package for the social sciences (SPSS) was used to collect data. The study sample reached (400) Syrian refugees paterfamilias included the both sexes selected by the intentional method. The study found that there was security, economic and social incentives that motivate the Syrian refugees to stay in Jordan, and security, economic and social incentives that motivate the Syrian refugees to return provided that they change over time. The study showed no differences among the study sample due to the variable of family income towards security, economic and social incentives to stay or return. In light of the results, the study recommended to economically integrate the Syrian refugees in the Jordanian market through providing them with an international financial support that achieves benefit to both host communities and refugees.